2009
DOI: 10.1016/j.neuropsychologia.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Attentional orienting induced by arrows and eye-gaze compared with an endogenous cue

Abstract: Exogenous orienting has been widely studied by using peripheral cues whereas endogenous orienting has been studied with directional central cues. However, recent evidence has shown that centrally presented eye-gaze and arrows may produce an automatic rather than voluntary orienting of attention. Therefore, the aim of the present study was to investigate the behavioural and electrophysiological (event-related potentials-ERP) correlates of the attentional shift induced by arrows and eye-gaze. In order to have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
100
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 103 publications
(132 reference statements)
23
100
2
Order By: Relevance
“…The choice of the task was based on the idea that, in real life, we most often use eye gaze to localize the source of the emotion before discriminating it. Our results are consistent with studies suggesting that attention orienting by gaze and arrows may recruit similar neural networks (e.g., Brignani et al, 2009), although to be conclusive, prospective studies will need to directly compare EDAN and ADAN components to arrow and gaze cues in the same paradigm. It is also important to note the larger Gaze laterality effect at ADAN than at EDAN.…”
Section: Erps To the Gaze Cuessupporting
confidence: 90%
See 1 more Smart Citation
“…The choice of the task was based on the idea that, in real life, we most often use eye gaze to localize the source of the emotion before discriminating it. Our results are consistent with studies suggesting that attention orienting by gaze and arrows may recruit similar neural networks (e.g., Brignani et al, 2009), although to be conclusive, prospective studies will need to directly compare EDAN and ADAN components to arrow and gaze cues in the same paradigm. It is also important to note the larger Gaze laterality effect at ADAN than at EDAN.…”
Section: Erps To the Gaze Cuessupporting
confidence: 90%
“…It was suggested that the processes at play in gaze-oriented attention are similar to those involved in arrow-oriented attention (e.g., Brignani, Guzzon, Marzi, & Miniussi, 2009). Thus, the two stages of attention, i.e., orienting toward a cued location and holding attention at that location, indexed, respectively, by EDAN and ADAN components in arrow cuing paradigms were expected.…”
Section: Erps To the Gaze Cuesmentioning
confidence: 99%
“…With respect to social attention, we propose that repeated association between observed gaze direction and relevant stimuli leads to the formation of a gaze cueing schema that allows very rapid orienting of spatial attention to the gazed-at location. This idea is a more formal expression of the view that social attention is the consequence of learned associations, rather than an innate response to biological stimuli (e.g., Brignani, Guzzon, Marzi, & Miniussi, 2009). The advantage of placing gaze cueing in this framework is that the factors that mediate the selection/deselection of schemas have been precisely specified by Cooper and Shallice (2000).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results suggest that, while both low-level physical properties of a stimulus and its emotional value influence the rapid allocation of attention, two separate mechanisms may be operating in parallel to increase neural processing of these different types of behaviorally relevant stimuli. Effects of exogenous attention may begin rapidly and primarily influence early stages of processing (fast attention orienting effect, see, e.g., Brignani, Guzzon, Marzi, & Miniussi, 2009), but be more short-lived; whereas the effects of emotional attention may be expressed at a slightly later onset and mainly impact on the visual encoding of the subsequent target T. Brosch et al / Neuropsychologia xxx (2011) xxx-xxx 7 as a function of the preceding emotional information at the same location (gain control effect, see Hillyard et al, 1998).…”
Section: Discussion Of Experimentsmentioning
confidence: 99%